Tall story - Gourlay, Candy (Cacho Pub. House, 2010)
Sixteen-year-old Bernardo, who is eight feet tall and suffers from a condition called Gigantism, leaves the Philipines to live with his mother's family in London, much to the delight of his thirteen-year-old half sister Andi, a passionate basketball player.